PELAKSANAAN TANGGUNGJAWAB NEGARA TERHADAP PERUBAHAN IKLIM BERDASARKAN PERJANJIAN PARIS 2015 - Nasution, Sharfina Azalia; Waryenti, Deli; Muthia, Arini Azka (UNIB Press, 2022)
Various natural disasters occur due to climate change caused by human activities. The international community's awareness of overcoming climate problems has been proven by ratifying the Paris Agreement 2015. Based on the background conditions, the problem is about state responsibilities for climate change and the implementation of these responsibilities before and after the Paris Agreement 2015. The research method used is normative law with a legal approach and conceptual approach. The results obtained: there are several state responsibilities contained in the Paris Agreement 2015, including reducing greenhouse gas emissions, carrying out environmental conservation, and avoiding losses from climate change. These can be done through mitigation and adaptation efforts, climate finance, development of technological mechanisms, international cooperation, and climate education. Although these responsibilities have been regulated but the implementation in countries has not been carried out optimally due to several obstacles, such as a lack of funding and technology skills. Keyword: Paris Agreement 2015, State Responsibility, Climate Change.